Conjunctive interpretation of core and log data through association of the effective and total porosity models - Worthington, P. F. (Core-Log Integration, 1998)
Traditionally, the deterministic open-hole petrophysical evaluation of non-Archie primary reservoirs has been undertaken exclusively within one or other of two intergranular systems, those of effective and total porosity. Yet, these interpretative models can be considered conjunctively with the object of inter-model validation of petrophysical interpretation. These considerations reveal ways of demonstrating the numerical compatibility of the two approaches. The compatibility is expressed in terms of equalities that contain core-calibrated, log-derived parameters and that are founded on the underlying petrophysics. The equalities must be satisfied if the petrophysical procedures are to be applied consistently and correctly. These inter-model algorithms constitute a basis for a proposed quality assurance scheme in well-log interpretation that goes beyond tying log data back to core. They suggest quality control points at which core-calibrated log data can be examined to assess the meaningfulness and performance of interpretation procedures at different stages of the petrophysical evaluation process. These assessments form a basis for the development of measures of confidence in the practice of open-hole well-log interpretation for porosity and hydrocarbon saturation, regardless of whether the interpretation is ultimately set in the context of the effective or the total porosity model. More generally, the subject matter forms part of a broader thrust to introduce a systematic quality assurance culture into open-hole petrophysical interpretation.